Development of Teaching Materials with Interactive Media for Speaking Skills Seventh Grade High School Students - Arifah, Bilqis; Munjiah, Ma'rifatul; Huda, Miftahul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Materials are a very important tool in the educational process. Good materials are designed to present the material in a systematic, engaging, and easy to understand manner for students. This writing to know how to develop materials for teaching speaking skills based on interactive means for seventh grade students in high school. The researcher used the development research method based on the ADDIE model. The ADDIE development model was developed by William Lee. The ADDIE model is a development model that contains systematic and simple stages. There are five stages in the ADDIE development model: analysis, design, development, implementation, and evaluation. The result of this research is the production of materials for teaching speaking skills based on interactive media. The development of materials for teaching speaking skills based on interactive media for seventh-grade high school students is carried out through five stages: (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation.